Vegetation management and restoration species safety with aminocyclopyrachlor - Getts, Thomas Jordan, author; Westra, Philip, advisor; Jacobi, William, committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2015)
Aminocyclopyrachlor is a synthetic auxin herbicide in the pyrimidine carboxylic acid family, and is the only herbicide within the family. Aminocyclopyrachlor exhibits excellent herbicide activity offering multiple year control of many broadleaf noxious weeds and many non-desirable tree species (DuPont 2009). A non-native tree, Russian olive is the fourth most common woody species in the western United States and has been shown to cause many detrimental ecological impacts. Removing Russian olive allows native species to reestablish within certain areas. Where the soil seed bank is depleted and there is not a native seed source nearby, planting restoration species can be desirable after invasive species removal. Biodiversity of native plant species can help support larger suites of desirable species within an ecosystem. Restoration is not just important after invasive species removal, but after disturbances such as mining, fire, and floods Two studies were conducted to investigate potential restoration uses of aminocyclopyrachlor within the Northern Front Range of Colorado. The objective of the first research project was to assess restoration species herbicide tolerance. Two types of tolerance were of interest; species soil residual herbicide tolerance, and species tolerance to foliar herbicide applications. The objective of the second research project was to determine the effectiveness of cut stump applications of aminocyclopyrachlor for the control large Russian olive trees. The first study evaluated the tolerance of eight monocot species and eight broadleaf species to thirteen soil residual herbicide treatments at two pre plant application timings and two post emergence application timings of sixteen herbicides. The study was located at the Colorado State University Horticultural Research Farm from 2010 to 2012. Initial percent frequency, relative change in percent frequency, and biomass were used to evaluate the tolerance of species tested. Variables were analyzed for each species, at each application timing, looking for differences among herbicide treatments. No difference in initial establishment percent frequency was detected for any species*herbicide combination compared to the untreated check (p>05). Relative percent frequency change from 2011 to 2012 was not significant compared to the untreated for any monocot species*herbicide combination (p>.05). However, differences were detected for dicot species*herbicide combinations (p<.05). No differences in biomass occurred for any species*herbicide combination compared to the untreated check (p>.05). Generally there were numerical trends in the data, suggesting monocot species were relatively tolerant to the herbicides tested at all four application timings. Numerically, percent frequency and biomass values indicated certain dicot species establishment was inhibited by certain soil residual herbicide treatments, and were completely removed by certain foliar herbicide applications. In general monocot species tested were more tolerant than dicot species tested, especially in the foliar treatments. However, many instances of monocot and dicot species tolerances to herbicide applications tested were found. This implies that when an herbicide is used to control an invasive species, many restoration species tolerant to the soil residual herbicide could be safely planted the following year. Additionally many restoration species were tolerant to foliar herbicide applications, indicating certain applications could be made to control non-planted weedy species during restoration species establishment. The second study assessed the effectiveness of Aminocyclopyrachlor, imazapyr, triclopyr and glyphosate for cut stump application control of Russian olive. Thirty nine replications of herbicide treatments were tested at three field sites in the Northern Urban Front Range of Colorado. Treatment mortality and off-target impact were assessed every six months for thirty months. Thirty months after treatment, glyphosate, aminocyclopyrachlor, imazapyr, triclopyr, and the untreated check had 95, 92, 74, 71, and 18 percent mortality of Russian olive trees. All herbicide treatments had higher mortality compared to the untreated check (p<.05), but no herbicides were different from one another (p>.05). Herbicide applications have the potential to cause injury to non-target vegetation. The bare soil around each stump was measured (Radius of Inhibition) to capture the off target impact of herbicide applications. Thirty months after treatment there was a radius of inhibition of 4 cm, 8 cm, 13 cm, and 26 cm for glyphosate, triclopyr, imazapyr, and aminocyclopyrachlor respectively. Aminocyclopyrachlor had a larger radius of inhibition than other herbicide treatments tested thirty months after application (p<.05). In order to treat an average size Russian olive within our study, the cost of herbicide products were $1.47, $1.98, $1.16, and $5.95 for glyphosate, triclopyr, imazapyr, and aminocyclopyrachlor respectively. Overall we found aminocyclopyrachlor offered Russian olive control comparable to other herbicides tested. However, it had the largest off target impact, and was three times the cost of the second most expensive treatment.
Keywords: cut stump; restoration planting; vegetation management; herbicide tolerance; aminocyclopyrachlor; Russian olive